2018
DOI: 10.5964/ijpr.v11i2.269
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of the short-form UCLA Loneliness Scale (ULS-6) among Palestinian university students

Abstract: The purpose of this research was to analyze the psychometric characteristics of the short-form UCLA Loneliness Scale (ULS-6) among Palestinian university students. The sample consisted of 288 university students (56% women and 44% men), aged 18-22 years. The psychometric characteristics of the ULS-6 were examined using confirmatory factor analysis, reliability analysis, and criterion-related validity methods. The unidimensionality of the ULS-6 was supported among Palestinian university students. The ULS-6 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
16
0
2
Order By: Relevance
“…Kim, , 1999bY. Kim et al, 2020;Knight et al, 1988;Kong et al, 2015;Kurina et al, 2011;Lamm & Stephan, 1987;Lee & Cagle, 2017;Lukács et al, 2019;Matthews-Ewald & Zullig, 2013;McWhirter, 1990;Nazzal et al, 2018;Neto, 2014;Niu et al, 2018;Oshagan & Allen, 1992;Park et al, 2019;Penning et al, 2014;Pretorius, 1993;Robinson-Whelen et al, 2016;Russell, 1996;Russell et al, 1980;Dan Russell et al, 1978;Saito et al, 2019;Sancho et al, 2020;Shi et al, 2016;Shorey et al, 2019;Solano, 1980;Stancliffe et al, 2014;Stephan et al, 1988;Steptoe et al, 2004;Sun & Chang, 2021;Velotti et al, 2021;Wang et al, 2018;Wang et al, 2001;Wilson et al, 1992;Wittenborn et al, 2020;Wongpakaran et al, 2020;Wu & Yao, 2008;Yu et al, 2020;Zakahi & Duran, 1982;Zarei et al, 2016). The PRISMA flow diagram of the study selection process with reasons for excluding studies is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim, , 1999bY. Kim et al, 2020;Knight et al, 1988;Kong et al, 2015;Kurina et al, 2011;Lamm & Stephan, 1987;Lee & Cagle, 2017;Lukács et al, 2019;Matthews-Ewald & Zullig, 2013;McWhirter, 1990;Nazzal et al, 2018;Neto, 2014;Niu et al, 2018;Oshagan & Allen, 1992;Park et al, 2019;Penning et al, 2014;Pretorius, 1993;Robinson-Whelen et al, 2016;Russell, 1996;Russell et al, 1980;Dan Russell et al, 1978;Saito et al, 2019;Sancho et al, 2020;Shi et al, 2016;Shorey et al, 2019;Solano, 1980;Stancliffe et al, 2014;Stephan et al, 1988;Steptoe et al, 2004;Sun & Chang, 2021;Velotti et al, 2021;Wang et al, 2018;Wang et al, 2001;Wilson et al, 1992;Wittenborn et al, 2020;Wongpakaran et al, 2020;Wu & Yao, 2008;Yu et al, 2020;Zakahi & Duran, 1982;Zarei et al, 2016). The PRISMA flow diagram of the study selection process with reasons for excluding studies is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The structural validity was assessed for all UCLA-LS versions except the original UCLA-20 (Dan Russell et al, 1978;Solano, 1980) and UCLA-5 (Lamm & Stephan, 1987). Based on the confirmatory factor (CFA) and Rasch analyses, high-quality evidence of sufficient structural validity was available for the UCLA-11 (Lee & Cagle, 2017) and UCLA-10 (all sub-versions) (Elphinstone, 2018; Knight et al, 1988;Russell, 1996) on a multidimensional scale (two-factor model) and the UCLA-7 (Allen & Oshagan, 1995;Elphinstone, 2018;Oshagan & Allen, 1992), UCLA-6 (Nazzal et al, 2018;Neto, 2014;Wongpakaran et al, 2020;Wu & Yao, 2008), and UCLA-4 (Elphinstone, 2018) on a unidimensional scale (one-factor model). Low to moderate-quality evidence of sufficient structural validity was available for the Revised UCLA-20 (Çinar & Toker, 2019;Dussault et al, 2009;Hartshorne, 1993;Park et al, 2019;Penning et al, 2014) and version 3 UCLA-20 (Boffo et al, 2012;Durak & Senol-Durak, 2010;Elphinstone, 2018;Russell, 1996;Sancho et al, 2020;Zarei et al, 2016) on a multidimensional scale (three-factor model) and for the UCLA-8 (Doğan et al, 2011;Elphinstone, 2018;Wu & Yao, 2008) on a unidimensional scale (one-factor model).…”
Section: Validity Of Long and Short Versions Of Ucla-lsmentioning
confidence: 99%
See 1 more Smart Citation
“…We asked 7 crowdsourcing workers on Mechanical Turk to label a random sample of 236 posts (made by 230 users) from the loneliness discussion board. Workers were shown a post, asked to imagine how they would feel had they wrote this post, and then answer the short-form ULS-6 to measure respondents' loneliness [44]. The ULS-6 is a widely used tool [45] for gauging the loneliness of respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Each item is answered on a 4-point scale ranging from 1 (never) to 4 (often). The ULS-6 was previously adapted to Palestinian culture (Nazzal, Cruz, & Neto, 2017).…”
Section: Lonelinessmentioning
confidence: 99%